Comparison of nasal and tracheobronchial clearance by similar techniques in normal subjects. - Millar, A B (1986)
Nasal and tracheobronchial mucociliary clearance have been compared in 10 healthy subjects. Nasal clearance was measured by monitoring the rate of removal of 2 microns diameter Teflon particles, labelled with 99mTc, which had been placed in the anterior part of the nose. Tracheobronchial clearance was measured with an objective radioaerosol technique, 5 microns diameter polystyrene particles being used. With these comparable techniques there was a close correlation between the nasal mucociliary clearance rate and both the area under the tracheobronchial clearance curve from 0 to 6 hours after radioaerosol inhalation (rs = -0.94, p less than 0.001) and the area under the tracheobronchial clearance curve from 0 to 2.5 hours after inhalation (rs = -0.79, p less than 0.01). The rate of clearance of small particles from the nose may thus be a useful guide to tracheobronchial clearance in healthy individuals.